Measurement of the effective atomic number of some transition and rare earth compounds using the Rayleigh to Compton scattering ratio of gamma radiation. Issue 7 (9th August 2017) - Hosamani, Mutturaj; Babu, S. Ramesh; Mirji, Santosh; Badiger, N. M.
ABSTRACT: The effective atomic numbers of some transition and rare earth compounds have been determined by measuring the ratio of Rayleigh to Compton scattering signal using 59.5 keV gamma radiation from americium-241 radioactive source. The scattered gamma photons from the elements and compounds at an angle of 90° were detected using an ORTEC high-purity germanium detector coupled with 16K multi-channel analyzer. By measuring the ratio of Rayleigh to Compton scattered signal (momentum transfer 3.38 Å −1 ), the effective atomic numbers of the transition and rare earth compounds have been determined and compared with theoretical values predicted by AutoZeff, power law, and direct method.